Inquérito soroepidemiológico da Leishmaniose visceral canina em Jaciara, Mato Grosso, Brasil - Lopes, Priscila Marcidelli (2012)
Visceral leishmaniasis (VL) is the most severe form of the disease Leishmaniasis group having the dog as a reservoir in urban areas. In Latin America, Brazil has the highest number of cases. Jaciara Cerrado Matogrossense, showed higher registration of dogs seropositive status (40%) and 14 in previous years up to 2011 human cases, with one death recorded, this data guided the design of this study aimed to determine the seroprevalence of canine visceral leishmaniasis (LVC) in urban and rural areas and to identify the risk factors involved in its transmission. The samples of canine serum occurred from June 2010 to May 2011. IFAT and ELISA techniques were used for serological detection of anti-Leishmania. Among the 345 samples analyzed, 296 in urban areas and 49 in rural areas, there has been a prevalence of 54.7%. The short-haired dogs and the aged 1-6 years had higher risk of infection, except domiciled in the rural area. Among the risk factors studied were more likely (p ≤ 0.05) dogs originating from the municipality itself with residence time over one year, with infestation, with planting fruit trees and vegetation. All these data characterize the observed urbanization and autochthony disease in Jaciara, and warn adopting control measures to minimize human and canine infection.